Protein Expression Profiling Predicts Graft Performance in Clinical Ex Vivo Lung Perfusion. Issue 3 (March 2015) - Machuca, Tiago N.; Cypel, Marcelo; Yeung, Jonathan C.; Bonato, Riccardo; Zamel, Ricardo; Chen, Manyin; Azad, Sassan; Hsin, Michael K.; Saito, Tomohito; Guan, Zehong; Waddell, Thomas K.; Liu, Mingyao; et al.
<x xml:space="preserve">Abstract</x> Objectives: To study the impact of ex vivo lung perfusion (EVLP) on cytokines, chemokines, and growth factors and their correlation with graft performance either during perfusion or after transplantation. Background: EVLP is a modern technique that preserves lungs on normothermia in a metabolically active state. The identification of biomarkers during clinical EVLP can contribute to the safe expansion of the donor pool. Methods: High-risk brain death donors and donors after cardiac death underwent 4 to 6 hours EVLP. Using a multiplex magnetic bead array assay, we evaluated analytes in perfusate samples collected at 1 hour and 4 hours of EVLP. Donor lungs were divided into 3 groups: (I) Control: bilateral transplantation with good early outcome [absence of primary graft dysfunction– (PGD) grade 3]; (II) PGD3: bilateral transplantation with PGD grade 3 anytime within 72 hours; (III) Declined: lungs unsuitable for transplantation after EVLP. Results: Of 50 cases included in this study, 27 were in Control group, 7 in PGD3, and 16 in Declined. From a total of 51 analytes, 34 were measurable in perfusates. The best marker to differentiate declined lungs from control lungs was stem cell growth factor -β [P < 0.001, AUC (area under the curve) = 0.86] at 1 hour. The best markers to differentiate PGD3 cases from controls were interleukin-8 (P < 0.001, AUC = 0.93) and growth-regulated oncogene-α (P = 0.001, AUC = 0.89) at 4 hours of EVLP. Conclusions: Perfusate protein expression during EVLP can differentiate lungs with good outcome from lungs PGD3 after transplantation. These perfusate biomarkers can be potentially used for more precise donor lung selection improving the outcomes of transplantation.